What we already know about the Post-COVID-19 Syndrome: A narrative review (Research, Society and Development, 2022)
As an increasingly number of patients recover from the acute COVID-19 disease, it has been observed that many face long lasting symptoms, referred as the Post-COVID-19 Syndrome. This article covers the most common signs and symptoms of this syndrome, its general aspects, and important complementary exams related to the disease. The manuscript is a narrative review, gathering new evidence published about the topic. The most common symptoms of the Post-COVID-19 Syndrome are chronic fatigue, breathlessness, depression or anxiety, pain, cough and alopecia, and many of them are still present 6 months after hospital discharge from the acute disease, depending on the gravity of the illness. It is important for patients to maintain medical follow-up to access severity of the symptoms and choose whether further investigation is necessary. There are some treatments available to some minimize the long-lasting burden of the syndrome, and the physician should access the need for treatment with the patient.  As a new disease, there is a lot of new evidence being produced rapidly, but no up-to-date protocol has already been published. Even with the vaccinations campaigns, the burden of the pandemic is yet out of sight, as it still killing thousands daily, and those who have recovered from the acute COVID-19 illness can present chronic symptoms. Therefore, we recommend health professionals to continuously up-to-date themselves, as new information is added to make better clinical decisions.